Tindak Tutur Ekspresif dalam Daftar Putar Maudy Ayunda’s Booklist “3 kunci Membangun Kekayaan” di Youtube - Dian Nurul Fitra; Dwi Praptiwi (BADAN PENERBIT STIEPARI PRESS, 2024)
An expressive attitude is a type of attitude that expresses something felt by the speaker. Expressive expression is understood not only through the expression but through gestures or movements performed by the communicator (source) to the communicant (receiver) to express his feelings. The purpose of this research is to find out what expressive expression Maudy Ayunda uses in her video entitled